Decision analysis supports the use of drain amylase-based enhanced recovery method after esophagectomy. Issue Volume 31:Issue10(2018) (10th May 2018) - Jiang, B; Ho, V P; Ginsberg, J; Fu, S J; Perry, Y; Argote-Greene, L; Linden, P A; Towe, C W
Summary: Postesophagectomy anastomotic leak is a common postsurgical complication. The current standard method of detecting leak is esophagram usually late in the postoperative period. Perianastomotic drain amylase level had shown promising results in early detection anastomosis leak. Previous studies have shown that postoperative day 4 amylase level is more specific and sensitive than esophagram. The purpose of this study is to determine if implementing a drain amylase-based screening method for anastomotic leak can reduce length of stay and hospital cost relative to a traditional esophagram-based pathway. The drain amylase protocol we propose uses postoperative day 4 drain amylase level to direct the initiation of PO intake and discharge. We designed a decision analysis tree using TreeAge Pro software to compare the drain amylase-based screening method to the standard of care, the esophagram. We performed a retrospective review of postesophagectomy patients from a tertiary academic medical center (University hospital Cleveland medical center) where amylase level was measured routinely postoperatively. The patients were separated into amylase-based pathway group and the standard of care group based on their postop management. The length of stay, costs, complications, and leak rate of these two groups were used to inform the decision analysis tree. In the base-case analysis, the decision analysis demonstrated that an amylase-based screening method can reduce the hospital stay by one day and reduced costs by ∼3, 000 compared to esophagram group. To take the variability of the data into consideration, we performed a Monte Carlo simulation. The result showed again a median saving of 0.71 days and ∼2, 500 per patient in hospital cost. A ballistic sensitivity analysis was performed to show that the sensitivity of postoperative day 4 amylase level in detecting a leak was the most important factor in the model. We conclude that implementing an amylase-based screening method for anastomotic leak in postesophagectomy patient can significantly reduce hospital cost and length of stay. This study demonstrates a novel protocol to improve postesophagectomy care. Based on this result, we believe a prospective multicenter study is appropriate.